Prevalence of Subclinical Hypothyroidism in Obese Adults Population - Ratan Kumar, Nasira Sohail, Muhammad Ziauddin, Saima Rafi, Merjan Hanif, Quratulain (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Determination of frequency of occurrence of subclinical hypothyroidism (SCH) in a local population of obese adults Study design: A cross-sectional study Place and Duration: This study was conducted at Sindh Government Lyari General Hospital Karachi from March 2022 to March2023 Methodology: The patients aged between 18 years to 55 years. All the participants had a body mass index (BMI)of more than 29 kg/m2. As per the exclusion criteria, those patients having kidney failure, liver failure, or already diagnosed with thyroid dysfunction, were not added to the study. Patients taking cholesterol-lowering drugs were also not considered in the study. A blood sample of all the patients was collected for the measurement of serum thyroxine levels and serum thyroid stimulating hormone (TSH) levels. Results: A total of 150 obese adults were considered in the study. The mean age of the participants was 35.7±8.1 years. Overall69 (46%) patients were male while 81 (54%) patients were females. The mean BMI of the patients was 32.1±2.1 kg/m2. The mean serum thyroxine level in the given population was 1.09±0.24 ng/dl and the mean serum TSH level was 3.12±1.09 mIU/L. A total of 24 (16%) patients were detected with subclinical hypothyroidism. Conclusion: Subclinical hypothyroidism is vastly prevalent in the obese adult population, particularly in adults with a BMI of more than 29 kg/m2. However, there is room for further studies to examine the correlation between obesity and SCH. Keywords: Subclinical Hypothyroidism, Obesity, TSH, Thyroxine, Body mass index